Evaluation of the Implementation Time of The Apbn/Apbd Project at The End of The Year With A Single-Year Budget - Mara Naek Pane; Azhar Azhar; Mardiaman Mardiaman (Syntax Corporation Indonesia, 2023)
In a project, it is necessary to have a work between owners and contractors that are used as a legal basis, in the form of construction contracts. One of these contracts is a contract for the procurement of goods and services based on the charge of its fiscal year consisting of a single-year contract which is the execution of a contract of work binding funds for 1 year while the contract of the plural year is a contract for the execution of work for a period of more than one fiscal year on the budget. Project delays almost occur every year and this results in huge losses for service users and service providers both in terms of finance and time. Project delays are divided into several types, namely: excusable delays, unforgivable delays, and delays that get compensation. Project delays are caused by several factors such as late payments and design changes. This factor greatly affects the performance of implementation in the field. The research process is carried out by conducting a survey. Starting with disseminating questionnaires to Owners, Contracts and outside parties as well as through literature studies, it is carried out to find out the comparison of the causes of project delays